The Long Noncoding RNA MEG3 Is Downregulated and Inversely Associated with VEGF Levels in Osteoarthritis. (21st May 2015) - Su, Wei; Xie, Wen; Shang, Qingkun; Su, Bing
Abstract : Osteoarthritis (OA) is becoming a major public health problem in China, especially considering the increase in average life expectancy of the population. Thus, enhanced understanding of the molecular changes associated with OA is urgently needed to develop more effective strategies for the diagnosis and treatment of this debilitating disease. LncRNAs play an important role in the processes of bone and cartilage development. Maternally expressed gene 3 (MEG3) is a maternally expressed lncRNA and may function as a tumor suppressor by inhibiting angiogenesis. OA is closely associated with angiogenesis and the inhibition of angiogenesis presents a novel therapeutic approach to reduce inflammation and pain in OA. In this study, we detected the mRNA expression of MEG3 and VEGF in articular cartilage samples from 20 OA patients and 10 healthy volunteers by real-time RT-PCR. VEGF protein is detected by ELISA in cartilage samples. The results show that human MEG3 is significantly downregulated in OA patients compared to normal cartilage samples. However, higher levels of VEGF mRNA and protein are found in OA compared to the control. Moreover, MEG3 levels are inversely associated with VEGF levels, suggesting that MEG3 may be involved in OA development through the regulation of angiogenesis.